Pengaruh Love of Money, Machiavellian, Idealisme dan Religiusitas pada Persepsi Etis Mahasiswa Akuntansi - Intan Kusumawathi Nikara, Ida Ayu Gde; Mimba, Ni Putu Sri Harta (E-Jurnal Akuntansi; Vol 26 No 1 (2019)DO - 10.24843/EJA.2019.v26.i01.p20, 2019)
The purpose of this study was to determine the effect of love of money, machiavellian, idealism and religiosity on the ethical perceptions of accounting students. The population of this study was S1 students of the non-regular accounting study program class of 2015 Faculty of Economics, Udayana University, Bali, amounting to 148 people, the samples taken amounted to 108 people. Instrument testing is done by validity and reliability testing. Before data analysis, a data analysis prerequisite test was conducted which consisted of normality test, multicollinearity test, and heteroscedasticity test. Data analysis used to test hypotheses is by using multiple linear regression analysis techniques. The analysis shows that love of money has a negative effect on ethical perceptions, machiavellian has a negative effect on ethical perception, idealism has a positive effect on ethical perception and religiosity has a positive effect on ethical perception. Keywords : love of money, machiavellian, idealism, religiosity, ethical perception